Hedging and Liquidity - Mello, Antonio S.; Parsons, John E. (Review of Financial Studies, 2000)
This article develops a model for evaluating alternative hedging strategies for financially constrained firms. A key advantage of the model is the ability to capture the intertemporal effects of hedging on the firm's financial situation. We characterize the optimal hedge. A wide range of alternative hedging strategies can be specified and the model allows us to determine in each case if the hedging strategy raises or lowers firms value and by how much. We show that hedging firm value, hedging cash flow from operations and hedging sales revenue are not optimal. The article highlights the fact that every hedging strategy comes packaged with a borrowing strategy which requires careful consideration.